Distribusi Gingivitis Pada Pasien Skizofrenia (Kajian pada RSJD Dr. Amino Gondohusodo Semarang) - Mikael Surya Editha; Lies Zubardiah (Fakultas Kedokteran Gigi Universitas Trisakti, 2020)
Background: Periodontal disease is a form of inflammation in the periodontal tissue commonly caused by bacteria. Periodontal disease consists of gingivitis and periodontitis. The clinical signs appears in gingivitis only occurs in the gingiva. The prevalence of periodontal disease in Indonesia in 2018 reached a number of 37,057%. Gingivitis can be occur to psychiatric disosder patient such as schizophrenia. Schizophrenia is a psychiatric disorder experienced by someone depicting the discordance or disharmony in the process of thinking, feeling, and doing. Normal individuals can easily learn the proper way to brush the teeth in order to wipe the plaque effectively. While, the brushing teeth education for schizophrenic patients is much harder to be accepted correctly. Objective: To identify the frequency distribution of gingivitis lesions in schizophrenic patients at the Regional Psychiatric Hospital Semarang. Method: The descriptive observational research was conducted by looking at the secondary data which was a medical record of schizophrenic patients experiencing dental treatment in the dental polyclinics during 2015-2019. Results: The undergoing dental treatment of schizophrenic patients were as many as 100 medical records. Gingivitis in schizophrenic patients are found 41% in most people ranged from 26 to 35 years old and 36 to 45 years old (63.42%). Based on gender, there are more men suffering from gingivitis lesions than women. Conclusion: A study shows that schizophrenia patients suffering gingivitis comes in a relatively high of number (41%).